(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
A pot experiment was conducted in the net house of the Department of Soil, Water and Environment, University of Dhaka to find out the interactive effects of nitrogen (0, 30, 60 and 120 kg/ha) and boron (0, 0.5, 1 and 2 kg/ha) fertilizers on the growth and nutrient contents of okra (Abelmoschus esculentus L.). The increase in height of okra was significant (p<0.05) due to combined application of nitrogen and boron fertilizers. Maximum height, shoot and root dry matter yield and uptake of nutrients in root and shoot of okra were observed in treatment 30 kg N/ha with 1 kg B/ha (N30Bi). But, higher doses of fertilizer combinations (60 and 120 kg of N/ ha with B) responded differently. Higher doses of fertilizer combinations significantly (p<0.05) reduced shoot and root growth as well as the concentration and uptake of nitrogen, phosphorus potassium in okra. It could be concluded that the treatment combination of 30 kg N/ha with 1 kg B/ha can be used for better growth of okra. Asiat. Soc. Bangladesh, Sci. 41(2): 173-181, December 2015